LOCAL WISDOM IN CREATING SIDETAPA VILLAGE AS A CULTURAL TOURISM DESTINATION IN BULELENG, BALI - Widiastini, Ni Made Ary; Darmawan, Komang Krishna; Wau, Rendy Syaputra (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study aims to explore in depth local wisdom in the transformation of the village into a cultural tourism destination, highlighting community involvement in maintaining traditions in the face of various pressures of tourism development. Become a tourist village since 2018, Sidetapa Village has been able to preserve its traditional and cultural values, despite the increase in tourist visits, especially foreign tourists from year to year, even staying in the village. To determine the interaction between cultural preservation and tourism, this study uses ethnographic methods that include community observation, interviews with community leaders and residents, and studying relevant documentation. The research findings reveal that the involvement of active roles of local residents in tourism management has implications for the ability of Sidetapa Village to maintain its cultural identity while generating economic benefits. By combining tourism activities with traditional values, the village has maintained cultural authenticity while encouraging community empowerment. The practices implemented by Sidetapa Village have shown that cultural sustainability and tourism progress can coexist if local genius, community involvement, and ethical tourism practices are combined.